Konsep Akhlak dalam Kitab Ta’lim Al-Muta’allim Karya Syaikh Burhanuddin Al-Zarnuji - Lisa Ulfa (Jurnal Pemikiran Islam, 2022)
One of the leading books written by Shaykh Burhanuddin al-Zarnuji is Ta'lim al-Muta'allim; this book is still a reference in the field of morality to this day. The contents of the book Ta'lim al-Muta'allim consist of learning methods, character education, and solutions to achieve success in taking education. This study uses a qualitative method; a relevant qualitative method approach is used to explore data sources in the book of Ta'lim al-Muta'allim Shaykh Burhanuddin al-Zarnuji. The results of the research are as follows: (1) Shaykh Burhanuddin sees that morality toward Allah SWT is something very important; this morality is reflected in a person through praying, hoping, and thanking Allah. (2) morals in respecting teachers, morals towards friends, morals in acquiring knowledge, and compassion for others; (3) morals towards oneself; here Shaykh Burhanuddin gives an explanation of how to respect yourself, think positively, respect time, and avoid reprehensible traits. Abstrak